Genetic and phenotypic parameters of first lactation and life time traits in Sahiwal cows - Sikandar Abbas; C.V. Singh; R.S. Barwal; C.B. Singh (Journal of Livestock Biodiversity, 2025)
The present study was conducted on first lactation and life time performance traits of Sahiwal cattle from Government Livestock Farm, Chakgangaria, Lucknow. First lactation and life time performance records of 927 Sahiwal cows born to 75 sires spread over a period of 28 years from 1978 – 2007 were utilized for the present study. The overall least squares mean of first lactation traits viz. AFC, FSP, FDP, FCI, FLMY, LTMY, PL and HL were estimated to be 1308.83 ± 11.65 days, 248.67 ± 4.94 days, 185.73 ± 50.50 days, 527.55 ± 4.93 days, 1424.23 ± 26.74 kg, 7943.38 ± 97.88 kg, 3277.93 ± 21.00 days and 3818.64 ± 23.54 days, respectively. Season effect was significant on most of the first lactation and life time production traits except first lactation milk yield. In contrast different periods of calving were found not to have significant influence on all the traits except life time milk yield. Similarly, sire effect was found significant on all the traits except first service period and first calving period. The heritability estimates of different first lactation and life time traits were low to high. The genetic and phenotypic correlations observed among all the traits were very low to high.